Magnetotelluric Inversion for Characterisation of Complex Aquifer Systems. Issue 1 (1st December 2018) - Schaa, Ralf; Harris, Brett; Pethick, Andrew; Costall, Alex; Pigois, Jon-Philippe; Takougang, Eric Takam
Abstract : Data from a magnetotelluric survey along a 2D transect across the basin-scale Badaminna Fault zone in the northern Central Perth Basin was used to augment the information from a limited number of monitoring wells across the fault zone. The magnetotelluric method was employed to provide continuous spatial information of the subsurface electrical resistivity for hydrogeological interpretation from the near surface to depths exceeding 2 km, where hydrostratigraphic units are offset by vertical fault displacement. Unconstrained 2D inversion resulted in a somewhat compartmentalized subsurface structure consistent with the known shallow hydrostratigraphy from borehole information, seismic and airborne EM. At larger depths broad conductive structures can be linked to increasing salinities.